On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism